Uma análise dos detalhes arquitetônicos da casa 78 da vila Bolonha, Belém-PA: a singularidade do engenheiro Francisco Bolonha - RAIOL, Ailla Caroline de Carvalho (2023)
The present work entitled An analysis of the House 78 of Bolonha Village in Belém-PA: The Singularity of the Engineer Francisco Bologna is a research about the characterization of the architectural details (decorative and constructive) that differentiate, individualize and singularize the House 78 of Vila Bologna in BelémPA, with the purpose of being subsidy for the preservation of the architectural heritage in question in case it will suffer future interventions. In Chapter I, a fundamental theoretical and historical approach is made clarifying the connections between Belle Époque, Eclectism and the engineer Francisco Bolonha, as well as inserting Bolonha Village and the House 78 in the studied context. In Chapter II, a spatial and construction system diagnosis of House 78 is made. Finally, in Chapter III, essential concepts are elucidated in the context of the preservation of cultural heritage: Preservation, Identity and Authenticity. In addition, a summary of the heritage charts pertinent to the present study is made to support the means of preservation.